Hubungan Disiplin dan Produktivitas Kerja Karyawan Dinas Pendidikan Kabupaten Pasaman - Kurnia Dwi Agustin; Hanif Alkadri; Rusdinal Rusdinal; Lusi Susanti (Journal of Educational Administration and Leadership, 2022)
This study aims to determine the relationship between discipline and work productivity on employees of the Pasaman Regency Education Office. The population of this research is all employees at the Education Office of Pasaman Regency, totaling 107 employees and the sample is 52 employees who are determined based on the Propionate Stratified Random Sampling technique. The instrument uses a Likert scale questionnaire that has been tried to observe the validity and reliability of the questionnaire. The result is a significant bond between discipline and work productivity of the Pasaman district education office employees.